A ‘panoptical’ or ‘synoptical’ approach to monitoring performance? Local public services in England and the widening accountability gap - Eckersley, Peter; Ferry, Laurence; Zakaria, Zamzulaila (Elsevier, 2014)
This article highlights how recent reforms to the auditing and assessment of local public services in England suggest there will be a shift from panoptical to ‘synoptical’ monitoring approaches. This is because the UK Government has abolished its centralised monitoring regime and instead required local authorities to publish a range of financial and performance datasets online, ostensibly so that citizens can hold organisations to account directly. However, the complexity and raw nature of these data, along with the sidelining of professional auditors, will result in most citizens being either unable or unwilling to undertake this task. As such, the proposed ‘synoptical’ approach will not materialise.Indeed, other legislative changes will mean that outsourcing firms effectively become the new, unaccountable observers of local public sector bodies within an enduring panoptical system. In many cases these companies will then assume responsibility for delivering the same services that they have assessed.